TRADISI SINAMOT DALAM PERKAWINAN ADAT SUKU BATAK TOBA DI KECAMATAN LIMO KOTA DEPOK - Ester Paulin Marbun (Universitas Sam Ratulangi, 2023)
Mating will continue to be carried out by humans with certain goals, reasons for implementation and the most basic is to carry out the process of regeneration or continue offspring. Marriages can be divided into customary marriages and non-customary marriages. Customary marriage is understood as a marriage based on customary rules that apply in the local community. Batak Toba traditional marriage is something that contains and produces rules, many values, principles, and certain ways that underlie life and growth in the community itself. In the traditional marriage process, there are conditions that must be done, namely the dowry given by the bridegroom to the bride in accordance with the customs and customs in the tribe, the dowry is called the term Sinamot. Sinamot tradition is the initial transaction process carried out by the Batak community as part of the procedure for marrying by the man to the woman. The Batak Toba people who live in Depok City, especially Limo District, still believe in the Sinamot tradition and still use it in a series of traditional marriages, even though they already have their own thoughts due to the environmental differences they face, but this is actually a challenge for the local Toba Batak tribe community to maintain and make the tradition a characteristic or identity that must be maintained. Keywords: sinamot tradition, traditional marriage, Batak Toba tribe